ROLE ANALYSIS OF ELABORATION LIKELIHOOD MODEL IN INFLUENCES OF PURCHASING INTERESTS BY ONLINE, EMPIRICAL STUDY IN AUTHENTICSTORESBY - Felicia Yvonne Reynaldy; Irantha Hendrika Kenang; Timotius F.C.W. Sutrisno (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
The number of online fraud is increasing in Indonesia, the main cause is customers who are tempted by low prices, so many online sellers are trying to increase consumer confidence by providing clear and complete information on their online stores. Through the Elaboration Likelihood Model theory, it will be seen whether customers prioritize emotions that will be represented by price sensitivity or affections represented by information transparency. This study aims to examine whether there is an influence between price sensitivity, information transparency, and buying interest for luxury goods. The object of this research is prospective buyers from AuthenticStoreSby. The sample collection method uses a purposive sampling of 130 people, which will be distributed online to Authenticstoresby followers in Indonesia. The SPSS application is used for multiple linear analysis of this study. The results of this study are price sensitivity and information transparency have a significant influence on consumer buying interest in luxury goods. However, information transparency does not significantly influence price sensitivity in luxury goods.